The Importance of Poetry in the Spiritual Education of Children (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
This article covers theoretical issues of raising children’s speech through poetry in preschool educational organization and family. In preschool organizations, he had a positive approach to the cultivation of children’s speech through poetry.